ANALISIS SECARA SIMULTAN BEBERAPA CAMPURAN PEMANIS PADA PRODUK MINUMAN RINGAN DENGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI - Situmeang, Tetty Uli (Jurnal Agritechno, 2024)
Beverages generally contain sweeteners, so it is necessary to develop methods to measure the levels of sweeteners in beverages. Several studies show that the use of sweeteners can trigger various diseases, so it is necessary to monitor their use in beverages. The purpose of this research was to develop and validate the analytical method and determine of acesulfame, sodium saccharin and aspartame in beverages samples in Medan city.This is experimental research using HPLC method with reversed phase by using Eclipse plus C18 column 250 x 4,6 mm, 5 μm, phosphate buffer mobile phase pH 5 : metanol (70:30), flow rate 1,0 ml/minute. The result of method validation showed that the linearity test have met the requirements with the coefficient of determination (R2), which is 0,99998 – 0,99999. The LOD values ranged from 0,0482 to 0,2482 mg/kg. The LOQ ranged from 0,1605 to 0,8273 mg/kg, and percent RSD of the repetability values ranges from 0,49% - 0,91% and intermediate precision is 0,24% - 0,63%. The result of percent recovery is an average of 93,59% - 105,28%. The proposed method has been successfully applied to the determination of the sweeteners in beverages products.